Revitalisasi Guru sebagai Pemimpin dalam Menanggapi Isu Perundungan melalui Pendidikan Karakter yang Progresif - Ikmah, Amit Dana; Setiawati, Ika; Neni, Titin Erviana Ayu (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Bullying is a serious problem in education that can have a negative impact on students' character development. Teacher revitalization in overcoming bullying is important in an effort to build a strong and positive character in children. This research aims to find out, revitalization of teachers as leaders in responding to the issue of bullying and follow-up on the revitalization of teachers as leaders in dealing with the issue of bullying through progressive character education.... The research method used is qualitative which involves the role of teachers in character education and handling bullying. The data collection techniques used are observation, interviews, and documentation. The data sources used came from teachers and students. The results of this study indicate that teachers have a significant role in shaping student character to reduce bullying that occurs in schools. Teachers involve students actively and take initiative, by forming discussion forums and developing anti-bullying programs students can feel comfortable and have an active role in creating a conducive learning environment.